Parametric Study of Sheet Pile Wall using ABAQUS - Taku Muni; Dipika Devi; Sukumar Baishya (Salehan Institute of Higher Education, 2021)
In the present study two-dimensional finite element analysis has been carried out on cantilever sheet pile wall using ABAQUS/Standard software to study the effect of different friction angles and its related parameters such as dilation angle, the interfacial friction coefficient between soil-wall on earth pressure distribution, and wall deformation. From the results obtained, it is found that there is a significant decrease in wall deformation with an increase in the angle of internal friction and its related parameters. The earth pressure results obtained from the finite element analysis shared a unique relationship with that of a conventional method. Both the results showed similar linear behavior up to a certain percentage of wall height and then changed drastically in lower portions of the wall. This trend of behavior is seen in both active as well as in passive earth pressure distribution for all the frictional angle. Hence, after comparing the differences that exist in the results for both methods, from the analysis a new relationship between the earth pressure coefficients from a conventional method and the finite element method has been developed for both active and passive earth pressure on either side of the sheet pile wall. This relationship so derived can be used to compute more reasonable earth pressure distributions for a sheet pile wall without carrying out a numerical analysis with a minimal time of computation. And also the earth pressure coefficient calculated from this governing equation can serve as a quick reference for any decision regarding the design of the sheet pile wall. Doi: 10.28991/cej-2021-03091638 Full Text: PDF